Effects of Rooibos tea, bottled water, and a carbohydrate beverage on blood and urinary measures of hydration after acute dehydration - Utter, A. C.; Quindry, J. C.; Emerenziani, G. P.; Valiente, S. (Research in Sports Medicine, 2010)
Rooibos tea contains polyphenol antioxidants, including flavonoids and phenolic acids that are potent free radical scavengers and has purported benefits for accelerated rehydration. The objective was to evaluate the effects of three different drinks (rooibos tea, bottled water, and a carbohydrate beverage) on blood and urinary markers of hydration after acute dehydration in collegiate wrestlers. Twenty-three athletes were recruited and followed a randomized, cross-over design with three different study arms comparing the effectiveness of rooibos tea, carbohydrate beverage (6% or 60 grams l-1), or bottled water (placebo) in promoting rehydration after a 3% reduction in body mass. Urine specific gravity (Usg) urine (Uosm) and plasma osmolarity (Posm), and plasma volume were measured pre- and post dehydration and at 1-h after rehydration. Statistical analyses utilized a 3 (conditions) 3 (times) repeated measures analysis of variance to test main effects. Significant interaction effects were found for Posm and Uosm, both of which remained below basleline after 1-h rehydration in the rooibos tea and water trials. No significant interaction effects were found for either urine Usg or plasma volume shift. The findings of this study demonstrate that rooibos tea was no more effective in promoting rehydration than plain water, with significant changes being found for Posm and Uosm in the carbohydrate/electrolyte solution, in collegiate wrestlers after a 3% reduction in body mass and a rehydration period of 1-h when consuming 100% of their body weight loss.